Customized image synthesis using diffusion models - Fu, Guanqiao (Nanyang Technological University, 2024)
Recently, diffusion models have become a powerful mainstream method for image generation. Text-to-image diffusion models, in particular, have been widely used to convert a natural language description (e.g., ‘an orange cat’) to photorealistic images (e.g., a photo of an orange cat). These pre-trained diffusion models have enabled various downstream applications, including customized image synthesis. For instance, a pre-trained text-to-image diffusion model can be leveraged to capture the appearance of a specific cat from multiple images, and subsequently generate images of this cat in diverse scenarios. In this final year project, we introduce an integration pipeline for storyboard generation. We begin by using large language models to assist in the creation of storylines, followed by the application of existing customization methods to visually render each scene. The pipeline is carefully designed to leverage both language models and customizastion methods for efficient and effective storyboard generation. We demonstrate the usefulness of our proposed pipeline both qualitatively and quantitatively. Additionally, a comprehensive research is also proposed focus on several diffusion models related to the latest advancements in customized image synthesis, which experimentally compare and analyze various diffusion models. We believe this project can enable and inspire subsequent explorations on applying customized image synthesis methods for automatic storyboard generation.